INFLUENCE OF HIGH SPEED OF CRYSTALLIZATION ON THE STRUCTURE OF ALUMINIUM ALLOYS - G. V. Dovnar; l. P. Dolgij; A. A. Andrits (Литьë и металлургия, 2010)
The aim of the work is development of new compositions of aluminium alloys with refractory metals of transition group and cremnium due to range extension of alloying at usage of high speed of melts cooling.